11th Hardwood Conference Proceedings - Beldean, Emanuela Carmen; Timar, Maria Cristina; Pop, Dana Mihaela (University of Sopron Press, 2024)
Clove (Eugenia carryophyllata) and thyme (Satureja hortensis) essential oils (C-EO, T-EO) have demonstrated their antifungal properties and might be useful in the field of wood conservation for remedial or preventive treatments. The present research aimed at studying the effect of pre-treatments of maple (Acer pseudoplatanus) wood surfaces with alcoholic solutions (10%) of C-EO and T-EO on their colour, subsequent coating with shellac or beeswax and the colour stability of the finished surfaces when exposed to artificial light simulating natural light filtered by window glass. Pre-treatments with essential oils of maple wood caused only small colour changes (E <3) under the experimental conditions. Coating with shellac changed totally the colour of all wood samples (E >30), slightly lower values for those pre-treated with T-EO and higher values for those pre-treated with CEO. The corresponding values for beeswax finishing were much lower, varying in the range 4.00-7.5, with the same trend. The light induced colour changes after 96 h exposure were almost similar for the uncoated wood samples, regardless the pre-treatment with essential oils. The colour changes of the samples pre-treated with T-EO and coated with shellac or beeswax were almost similar or slightly lower compared to those measured for the controls without pre-treatment. Contrarily, pre-treatments with CEO resulted in increased light induced colour changes of the coated surfaces, with about 3 units for shellac and 14 units for beeswax. This might be explained by the photo-induced oxidation of eugenol, the main component of C-EO, resulting in formation of new chromophores with quinoid structures, as supported by FTIR. These changes are more visible through the thinned, nearly colourless beeswax film.
Influence of pretreatments with essential oils on the colour and light resistance of maple (Acer pseudoplatanus) wood surfaces coated with shellac and beeswax
Keywords: wood; essential oils; colour; shellac; beeswax; light exposure; colour changes; FTIR